منهج تعليمي وفق تمرينات الرشاقة والتوازن بالاسلوب التدريبي وأثره في تعلم بعض مهارات الجمناستك الايقاعي للطالبات - غريب, فرهنگ فرج حممد; عبدالكريم, ڤيان; احمد, جلال خضر (Sulaimani Journal for Humanities, 2018)
The aim of the research was to identify the importance of fitness and balance exercises for students of the Faculty of Physical Education at the University of Sulaymaniyah. They used the experimental method to suit the nature of the research and relied on the one-set design with tribal and post-test. The sample consisted of students of the third school year, (4) weeks and two units per week and after the post-tests. The researchers reached some results, including the educational curriculum according to fitness exercises and balance had a clear impact on the improvement of some skills especially for effective and recommended for use during the learning and teaching process